SUNNI: MAKNA, ACUAN DAN RAGAM - Zainul Maarif (Journal of Islamic Studies and Humanities, 2018)
Sunni or Sunnism stands for Ahlu As-Sunnah wa al-Jamā`ah which is also called ASWAJA. Many people publish and debate it without clear meaning and reference. This article is a demonstrative-linguistic study that outlines the meaning and reference to the term "Sunni" to understand it clearly. This research shows that Sunnis have at least two groups. First, Sunni Ahlu Al- Ḥadīts, the path of Ibn Hanbal and Ibn Taimiyyah, which tends to be puritan and at some point raises hardline intolerant Muslims. Second, moderate Sunnis, who opened the space for fiqh schools other than Ibn Hanbal, and chooses to refer to moderate Islamic thinkers, such as Ash-Shāfi'i in fiqh (Islamic law), Al-Asy`ari in kalam (Islamic theology) and Al -Ghazali in Sufism (Islamic mysticism). The two Sunni groups were both Ahlu as-Sunnah wa al-Jamā`ah. The first group tends to embody the phrase Ahlu as-Sunnah wa al-Jamā'ah terminologically (iṣṭilāḥan), while the second group tends to display the phrase linguistically (lughatan). AbstrakSunni atau Sunnisme adalah singkatan dari Ahlu As-Sunnah wa al-Jamā`ah yang disebut juga dengan ASWAJA. Banyak orang yang mempublikasikan dan memperdebatkannya tanpa makna dan acuan jelas. Artikel ini adalah kajian demonstratif-linguistik yang mengurai makna dan acuan term “Sunni” untuk mengetahuinya secara jelas. Hasil peneltian menunjukkan bahwa bahwa Sunni sedikitnya ada dua kelompok. Pertama, Sunni Ahlu Al-Ḥadīts jalur Ibn Hanbal dan Ibn Taimiyyah, yang cenderung puritan dan pada titik tertentu memunculkan muslim-muslim garis keras yang tidak toleran. Kedua, Sunni moderat, yang membuka ruang bagi madzhab fikih selain Ibn Hanbal, dan memilih merujuk pada para pemikir Islam moderat, seperti Asy-Syafi`i dalam fikih (hukum Islam), Al-Asy`ari dalam kalam (teologi Islam) dan Al-Ghazali dalam tasawuf (mistisisme Islam). Dua kelompok Sunni tersebut sama-sama Ahlu as-Sunnah wa al-Jamā`ah. Kelompok pertama cenderung mengejawantahkan frase Ahlu as-Sunnah wa al-Jamā`ah secara terminologis (iṣṭilāḥan), sementara kelompok kedua cenderung menampilkan frase tersebut secara linguistik (lughatan).